PEMBIAKAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA MEDIA TANDAN KOSONG KELAPA SAWIT DAN SERBUK GERGAJI KAYU - DIBISONO, MUHAMMAD YUSUF; Gunawan, Hari; Ginting, Makhrani Sari; Abdi Kusuma (Agro Estate, 2023)
The aim of this study was to determine the effects of oil palm empty bunches (OPEFB) and sawdust as growing media for the growth of white oyster mushroom (Pleurotus ostreatus). This study was conducted at an oyster mushroom cultivation farm located at Jl. STM Ujung Medan, from October 2020 to January 2021. The experimental design was a randomized completely block design (RCBD) with one factor, namely the composition of the growing medium (oil palm empty bunches and sawdust) with 3 levels of treatment; S1 : 100% wood sawdust, S2 : 100% OPEFB, and S3 : 50% OPEFB + 50% wood sawdust. The observation included the mycelium initial growth time (days), fruits body growing time (days), hood width (cm), body diameter (cm), length of stalk (cm), and wet weight of the white oyster mushrooms after harvesting (g). The results showed that the treatment of OPEFB and sawdust had no significant effect on the mycelium initial growth time, body growth time, white oyster mushroom body diameter, white oyster mushroom stalk length, and the wet weight of white oyster mushrooms after harvesting. This result indicates that OPEFB can be used as an alternative growing media for cultivating white oyster mushroom, it can be single or combined with wood sawdust.